(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Populismo e religione: Libertà di autoespressione, politica, modernità, caratteristiche procedurali ABSTRACT: The article is devoted to the topic of populism in religion in modern conditions. The article explains the correlation between freedom of expression and populism. The authors consider the phenomenon of populism in various aspects, including: populism as an instrument of politicization of a religious organization, populism as a latent component of internally sacralized (though outwardly neutral) politics. For many centuries, the ruling regimes of various states have sought and tried to put the Church at the service of their political interests, trying to use the churches in their own domestic and even foreign policy games, related attempts to manipulate religious identities and engage in artificial "church-building", to turn churches into handy ideological tools in the service of power - all this was a hybridization of political populism and religious populism tailored to it. But under such conditions, religious populism is always a forced imposition of tendencies destructive to the Church, it is always a profanation of the religious, the destruction of the most fundamental foundations of religion. But equally, the Church must be protected on the other side - from populist attempts to infringe on the Church’s corpus of values, on relics and names honored by the rhetoric of freedom of expression. The authors conclude that populism (as a socio-legal tool, which is based on the paradigm of populism) should be used very cautiously - in the sphere of religion in a secular state. SUMMARY: 1. Introduction - 2. Populism. General concept, characteristic features, ontology - 2.1. The concept of populism - 2.2. Populism as a concept - 2.3. Populism as ideology - 2.4. Characteristic features and elements of populism - 2.5. Taxonomic diversity of populism - 2.6. Populism and democracy - 3. Religion and populism - 3.1. Religious populism as subtype of populism - 3.2. Freedom of expression and populism - 3.3. Populism as a tool of politicization of a religious organization - 3.4. Populism as a latent component of implicitly sacralized (albeit explicitly neutral) politics - 4. Conclusion.